Rapid mimicry of trunk and head movements during play in African Savanna elephants (Loxodonta africana) - Giada Cordoni; Martin Hecker; Valentina Crippa; Beatriz Gallego Aldama; Santiago Borragán Santos; Ivan Norscia (Scientific Reports)
Abstract The basic forms of motor and possibly emotion replication include behavioral contagion and rapid motor mimicry (RMM). RMM—mainly demonstrated during play—occurs when an individual perceives and rapidly (< 1 s) replicates the exact motor sequence of another individual. We collected data on an African Savanna Elephant (Loxodonta africana; N = 15) group housed at the Parque de la Naturaleza de Cabárceno (Spain) on play target movements of both trunk and head. We demonstrated the presence of RMM. Elephants that were more prone in mimicking others’ target movements were also more prone to play after observing others playing. RMM—as behavioral contagion—can enhance action coordination between players. As RMM was associated with more offensive play patterns than unreplicated target movements, RMM may allow competitive play sessions to occur, possibly replacing agonistic interactions. Neither individual (age, sex) nor social (affiliation levels) factors modulated the RMM. These findings can be related to the elephant high tolerance levels and the wide presence of play across age (including adults) and sex. Concluding, African elephants have the potential to share their affective states (emotional contagion) via RMM which is relevant to the investigation of the evolution of empathy in mammals including humans.